Manajemen Pembinaan Prestasi Sepak Bola Nusaina Fc. U-17 Tulehu Kecamatan Salahutu Kabupaten Maluku Tengah - Mesak Hattu (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research departs from the idea that an organization, even a football club, which is managed with good coaching management, certainly produces outstanding soccer players or athletes. This study aims to describe the management of Nusaina FC football achievement development. U-17 Tulehu, Salahutu subdistrict, Central Maluku district. This research is a naturalistic descriptive research using a qualitative approach (qualitative research). The subjects of this study were the coaches, administrators and athletes of the Nusaina FC football club. U-17 Tulehu, Salahutu subdistrict, Central Maluku district. The researcher acts as the main instrument in the data collection process. Data collection uses observation techniques, in-depth interviews and documentation. The data analysis technique used is an interactive analysis model, Milles & Huberman includes four main activities namely; data collection, data reduction, data presentation and drawing conclusions or verification. The level of trust (validity) of the data obtained was carried out using the following techniques: credibility (source and method triangulation, member checks and peer discussions), transferability, dependability and confirmability. The results of this study indicate that, 1) the management of the club organization is carried out according to the function of club management, 2) the recruitment of athletes is carried out by means of prospective athletes registering by submitting a copy of the birth certificate, family card, and statement letter, 3) Nusaina FC coach. U-17 Tulehu has a certificate as a trainer and the quality of the trainers can be said to be good, 4) the implementation of the training program has been programmed and planned, 5) the facilities and infrastructure owned are quite adequate, 6) the achievements obtained are very good at the district, provincial and national levels.